2015
DOI: 10.1038/nature15733
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular wiring enables electron transfer between methanotrophic archaea and bacteria

Abstract: The anaerobic oxidation of methane (AOM) with sulfate controls the emission of the greenhouse gas methane from the ocean floor. In marine sediments, AOM is performed by dual-species consortia of anaerobic methanotrophic archaea (ANME) and sulfate-reducing bacteria (SRB) inhabiting the methane-sulfate transition zone. The biochemical pathways and biological adaptations enabling this globally relevant process are not fully understood. Here we study the syntrophic interaction in thermophilic AOM (TAOM) between AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
428
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 459 publications
(470 citation statements)
references
References 53 publications
(16 reference statements)
20
428
2
Order By: Relevance
“…e-Pili have been proposed to wire an anaerobic methane oxidizer of the ANME-1 phylogenetic group to the sulfate-reducer Desulfofervidus auxilii for DIET (Krukenberg et al 2016, Wegener et al 2015. It was not possible for us to obtain a sample of the consortium to directly evaluate the conductivity of the pili, but G. sulfurreducens readily expressed pili ( Figure 4D) from the Do.…”
Section: Pilin Of Desulfofervidus Auxilii Does Not Yield E-pilimentioning
confidence: 99%
See 2 more Smart Citations
“…e-Pili have been proposed to wire an anaerobic methane oxidizer of the ANME-1 phylogenetic group to the sulfate-reducer Desulfofervidus auxilii for DIET (Krukenberg et al 2016, Wegener et al 2015. It was not possible for us to obtain a sample of the consortium to directly evaluate the conductivity of the pili, but G. sulfurreducens readily expressed pili ( Figure 4D) from the Do.…”
Section: Pilin Of Desulfofervidus Auxilii Does Not Yield E-pilimentioning
confidence: 99%
“…For example, it was suggested that e-pili were involved in DIET in a consortium of an ANME-1 microbe and its sulfate-reducing partner (Wegener et al 2015). The sulfate-reducing partner highly expressed a pilin gene when the two microorganisms were growing syntrophically and pili-like filaments were abundant in the co-culture (Wegener et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from interspecies electron transfer, MNWs have also been implicated in electron transfer between bacteria and archaea (Wegener et al, 2015). Further, cyanobacteria are an important constituent of the microbial mat and it is hypothesized that cyanobacterial MNWs can transfer electrons to other micro-organisms present in the microbial mat (Gorby et al, 2006;Lea-Smith et al, 2015).…”
Section: Microbial Nanowirementioning
confidence: 99%
“…MNWs have been believed to play a role in methane production in syntrophic microbial communities (Morita et al, 2011;Rotaru et al, 2014;Summers et al, 2010;Wegener et al, 2015), which can be exploited further for improved methane production in anaerobic digesters. Interested readers are referred to specific reviews on this topic (Lovley, 2011;.…”
Section: Bioenergymentioning
confidence: 99%